Portfolio and financing adjustments for U.S. banks: Some empirical evidence - Krainer, Robert (Journal of Financial Stability, 2009)
This paper presents a model of the portfolio and financing adjustments of U.S. banks over the business cycle. At the core of the model is a moral hazard problem between depositors/bank regulators and stockholders. The solution to this problem takes the form of shared management of the bank. Stockholders manage the bank's portfolio and the regulator manages the financing of the portfolio. The model predicts that portfolio adjustments are made to conform to the risk aversion of shareholders and financing adjustments are made to offset changes in portfolio risk. Regression evidence for 1955–2000 fails to reject these predictions.